Space 98 : (ASCE, 1998)
Space 98: Proceedings of the Sixth International Conference and Exposition on Engineering, Construction, and Operations in Space was organized with the intent to encourage and stimulate planning, positive and productive interactions, and development of needed technologies and expertise for exploration of space and working in challenging terrestrial environments.